2016
DOI: 10.1007/s00484-016-1175-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent warming evidence inferred from a tree-ring-based winter-half year minimum temperature reconstruction in northwestern Yichang, South Central China, and its relation to the large-scale circulation anomalies

Abstract: High-resolution winter temperature reconstructions in China are rare, yet vital for the comprehensive understanding of past climate change. In the present work, the first winter-half year minimum mean temperature from previous November to current April in northwestern Yichang, South Central China, was reconstructed back to 1875 based on tree-ring material. The reconstruction can explain 55 % of the variance over the calibration period during 1955-2011. The temperature maintained at comparatively low level befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The decadal scale has been the primary interest in paleoclimate studies. Previous studies have revealed that the low-frequency variation in the reconstruction is more reliable than the high-frequency variation [43]. To highlight decadal scale variation, an 11-year moving average was applied in data analysis [44].…”
Section: Methodsmentioning
confidence: 99%
“…The decadal scale has been the primary interest in paleoclimate studies. Previous studies have revealed that the low-frequency variation in the reconstruction is more reliable than the high-frequency variation [43]. To highlight decadal scale variation, an 11-year moving average was applied in data analysis [44].…”
Section: Methodsmentioning
confidence: 99%
“…The results suggested that these three types of TCCI changes are all affected by the sea surface temperatures of the Pacific, Indian, and Atlantic Ocean, especially the high and medium levels of TCCI types. The study found that most of the Indian Ocean and the western Pacific region is the key region affecting the climate of China and East Asia [62]. At the same time, many studies have also found that the thermal state of the North Atlantic and the convective activity over it play a very important role in modulating climate change in the surrounding areas, and even in East Asia, through the Atlantic Interdecadal Oscillation and the North Atlantic Oscillation [58,63].…”
Section: Analysis Of Driving Forces Of the Tcci In The Study Areamentioning
confidence: 99%
“…In the third topographical step, the temperature data in the winter half-year weakly reflect the warming in the twentieth century [ 66 , 67 ], but some data do not reflect this warming [ 69 ]. This situation must be taken into consideration when building a regional model of temperature changes.…”
Section: Region With An Api Greater Than 600 MMmentioning
confidence: 99%
“…This situation must be taken into consideration when building a regional model of temperature changes. Studies have shown that the reconstructed winter temperature in this area is mainly affected by the Asian winter monsoon [ 69 ], the atmospheric circulation at 500-hPa terrain height and the Siberian High [ 67 ].…”
Section: Region With An Api Greater Than 600 MMmentioning
confidence: 99%